Dampak Pelayanan Gofood Terhadap Penjualan Unit Usaha Mikro Makanan Lokal Mitra Gofood di Kota Bandung - Salman Hafidz; Caria Ningsih; Ilham Fajri (Tourism Scientific Journal, 2021)
At this time the digital world has entered all sectors of life, the tourism sector for example with the google maps application to show tourist locations, hotel booking applications, and online transportation applications and food delivery services. Gofood is one of the food delivery services found on the Gojek application. With the presence of Gofood tourists who are in tourist destinations or lodging, especially in the city of Bandung can easily order local specialties or popular culinary in the city of Bandung. The purpose of this study was to determine the effect of Gofood services on increasing sales from local Gofood partner micro food businesses in the city of Bandung. This study uses quantitative methods using simple linear regression analysis, F-test and t-test. The results showed that the Gofood service variable was positive and significant and had an effect of 42.4% on the sales of Gofood partner local micro food businesses in the city of Bandung, the remaining 57.6% was the influence of variables not examined such as product quality, price, marketing management, mix marketing, etc. Gofood partner capital conditions are relatively increased by accumulation, but for daily capital, especially weekends (Friday, Saturday, Sunday, and national holidays) constrained because the disbursement of sales on that day only distributed to partners on Monday and above 12 noon, preferably in accelerate the disbursement because it affects the daily capital turnover.